A novel cortical biomarker signature for predicting pain sensitivity: protocol for the PREDICT longitudinal analytical validation study. (27th July 2020) - Seminowicz, David A.; Bilska, Katarzyna; Chowdhury, Nahian S.; Skippen, Patrick; Millard, Samantha K.; Chiang, Alan K.I.; Chen, Shuo; Furman, Andrew J.; Schabrun, Siobhan M.
Abstract : PREDICT will undertake analytical validation of a peak alpha frequency and corticomotor excitability biomarker, determining the sensitivity, specificity, and accuracy at predicting pain sensitivity. Abstract: Introduction: Temporomandibular disorder is a common musculoskeletal pain condition with development of chronic symptoms in 49% of patients. Although a number of biological factors have shown an association with chronic temporomandibular disorder in cross-sectional and case control studies, there are currently no biomarkers that can predict the development of chronic symptoms. The PREDICT study aims to undertake analytical validation of a novel peak alpha frequency (PAF) and corticomotor excitability (CME) biomarker signature using a human model of the transition to sustained myofascial temporomandibular pain (masseter intramuscular injection of nerve growth factor [NGF]). This article describes, a priori, the methods and analysis plan. Methods: This study uses a multisite longitudinal, experimental study to follow individuals for a period of 30 days as they progressively develop and experience complete resolution of NGF-induced muscle pain. One hundred fifty healthy participants will be recruited. Participants will complete twice daily electronic pain diaries from day 0 to day 30 and undergo assessment of pressure pain thresholds, and recording of PAF and CME on days 0, 2, and 5. Intramuscular injection of NGF will be given into the right masseter muscle on days 0 and 2. The primary outcome is pain sensitivity. Perspective: PREDICT is the first study to undertake analytical validation of a PAF and CME biomarker signature. The study will determine the sensitivity, specificity, and accuracy of the biomarker signature to predict an individual's sensitivity to pain. Registration details: ClinicalTrials.gov: NCT04241562 (prospective).